Incubation Time of Liquid Organic Fertilizers and Doses of Nitrogen on Growth and Yield of Cherry Tomatoes (Lycopersicum esculentum) - Widjajanto, Didik Wisnu; Kriswijayanto, Triyoga Budi; Sumarsono (Jurnal Online Pertanian Tropik, 2020)
ABSTRACT The aim of the experiment was to evaluate the effect of incubation time of liquid organic fertilizer and nitrogen doses on the growth and production of cherry tomatoes. The experiment was conducted at the sreen house of Department of Agriculture of Semarang City and at the Ecology and Crop Production Laboratory of the Faculty of Animal and Agricultural Sciences, Diponegoro University from May-September 2017. A completely randomized design of 3x3 factorial patterns was used throughout the experiment. The first factor consisted of the incubation time of liquid organic fertilizer 6, 12 and 18 days, respectively for I1, I2 and 13 treatments. The second factor was the doses of nitrogen that consisted of three levels 36, 72 and 180 kgN/ha as D1, D2 and D3 treatments, respectively. Observed data included plant height, fresh and dry weight of stover, harvest index, fruit production and fruit sets. Obtained data were analyzed statistically by using ANOVA and continued with the smallest significant difference test at 5%. On the basis of the experiment it may be concluded that all of LOF with different of incubation time at dose of 72 kg N/ha may be recommended for cherry tomatoes cultivation.